Effects of nitrogen impurities on the microstructure and electronic properties of P-doped Si nanocrystals emebedded in silicon-rich SiNx films. (May 2016) - Ma, Deng-Hao; Zhang, Wei-Jia; Luo, Rui-Ying; Jiang, Zhao-Yi; Ma, Qiang; Ma, Xiao-Bo; Fan, Zhi-Qiang; Song, Deng-Yuan; Zhang, Lei
Abstract: Phosphorus doped Si nanocrystals (SNCs) emebedded in silicon-rich SiN x :H films were prepared using plasma enhanced chemical vapor deposition technique, and the effects of nitrogen incorporation on the microstructure and electronic properties of the thin films have been systematically studied. Transmission electron microscope and Raman observation revealed that nitrogen incorporation prevents the growth of Si nanocrystals, and that their sizes can be adjusted by varying the flow rate of NH3 . The reduction of photoluminescence (PL) intensity in the range of 2.1–2.6 eV of photon energy was observed with increasing nitrogen impurity, and a maximal PL intensity in the range 1.6–2.0 eV was obtained when the incorporation flow ratio NH3 /(SiH4 +H2 +PH3 ) was 0.02. The conductivity of the films is improved by means of proper nitrogen impurity doping, and proper doping causes the interface charge density of the heterojunction (H-J) device to be lower than the nc-Si:H/c-Si H-J device. As a result, the proper incorporation of nitrogen could not only reduce the silicon banding bond density, but also fill some carrier capture centers, and suppress the nonradiative recombination of electrons. Highlights: Proper nitrogen incorporation improved the conductivity of the prepared film. Interface defect states of nanocrystalline silicon were reduced with nitrogen incorporation. Proper nitrogen incorporation could enhance the I–V characteristic of the heterojunction device.